2011
DOI: 10.1111/j.1469-8137.2010.03633.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular pH measurements in Emiliania huxleyi reveal pronounced membrane proton permeability

Abstract: Key words: acid-base metabolism, BCECF (2¢,7¢-bis-(2-carboxyethyl)-5-(and-6)-carboxyfluorescein), bicarbonate transport, dissolved inorganic carbon (DIC), DIDS (4,4¢-diisothiocyanatostilbene-2,2¢-disulfonic acid), Emiliania huxleyi, nigericin, pH homeostasis. Summary• To understand the influence of changing surface ocean pH and carbonate chemistry on the coccolithophore Emiliania huxleyi, it is necessary to characterize mechanisms involved in pH homeostasis and ion transport.• Here, we measured effects of chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 45 publications
(97 reference statements)
2
89
0
Order By: Relevance
“…2b). Decreased C i affinities in response to elevated P CO 2 have been reported for diploid E. huxleyi (strain PLYB92/11; Rost et al 2003), a number of diatoms (Trimborn et al 2008), and also cyanobacteria (Sü ltemeyer et al 1998). The latter study suggests posttranslational modification being responsible for decreased affinities under elevated P CO 2 .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…2b). Decreased C i affinities in response to elevated P CO 2 have been reported for diploid E. huxleyi (strain PLYB92/11; Rost et al 2003), a number of diatoms (Trimborn et al 2008), and also cyanobacteria (Sü ltemeyer et al 1998). The latter study suggests posttranslational modification being responsible for decreased affinities under elevated P CO 2 .…”
Section: Discussionmentioning
confidence: 60%
“…Also, these processes might be responsive to [H + ] rather than C i concentrations (Taylor et al 2010;Lefebvre et al 2012). Suffrian et al (2011) have shown that external pH perturbations translate linearly into cytoplasmic pH changes. An impairment of transport processes (e.g., for DIC and Ca 2+ ) due to low internal pH might weaken the process of biomineralization.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, malformations found in our study are also resulting from a malfunctioning of the cytoskeleton, in our case with the chemical driving force being H + . This explanation seems plausible since H + is known to easily enter into the cytosol of E. huxleyi (Suffrian et al, 2011). Here, a change in [H + ] could disturb the correct functioning of cytoskeleton elements or the enzymes associated with them so that the controlled expansion of the CV is handicapped (Langer et al, 2006).…”
Section: Cause Of Malformationsmentioning
confidence: 99%
“…Four to five control and treatment larvae were measured in an alternate mode and used for further analysis. Nigericin was used to calibrate pH i of living cells as previously described by Suffrian et al (68). PMCs of pluteus larvae were exposed to 10 μmol·L −1 nigericin in the presence of 150 mmol·L −1 K + at pH 5.5, 6.5, 7, 7.5, and 8.5.…”
Section: Methodsmentioning
confidence: 99%